Estimating Taxable Income Responses using Danish Tax Reforms - Henrik Jacobsen Kleven; Esben Anton Schultz (University of Copenhagen, Economic Policy Research Unit (EPRU), 2011)
This paper presents evidence on taxable income responses using administrative data that link tax return information to detailed socioeconomic information for the entire Danish population over 25 years. The identifying variation is provided by a series of tax reforms that create large tax variation across individuals, income forms, and over time. It is argued that the unique tax variation and data in Denmark makes it possible to control for the biases from non-tax changes in the income distribution and mean reversion that plague much of the existing literature. Our main findings are the following: (i ) Labor income elasticities are modest overall, around 0.05 for wage earners and 0.10 for self-employed individuals. (ii ) Capital income elasticities are about 2-3 times larger than labor income elasticities. (iii ) Behavioral elasticities are much larger when estimated from large tax reform episodes than for small tax reform episodes, consistent with idea that responses to small tax changes are attenuated by optimization frictions such as adjustment costs and inattention. (iv) Crosstax effects between labor and capital incomefor example due to income shiftingare in general small. (v) All of our findings are extremely robust to specification (such as pre-reform income controls), suggesting that we have controlled in a sufficiently rich way for non-tax factors impacting on taxable income.
Keywords: H24; H31; J22; 330; Steuerreform; Steuerwirkung; Einkommenselastizität; Dänemark